COMPENSATION–IRRITATION MATRIX (CIM): RECONSTRUCTION AND MATHEMATICAL AND ALGORITHMIC VALIDATION OF THE FUNCTIONAL MOVEMENT SCREEN (FMS) SCORING SYSTEM - Chen Zhao; Rui He; WeiBo Shang; JunJie Zheng; RongJin He; FangHao Li (World Journal of Clinical Sciences, 2026)
The Functional Movement Screening (FMS) composite score (0-21 points) is achieved merely by adding up the scores of seven tests, and by implication, it assumes that all deductions (pain, severe restriction, compensation) are equal in numerical terms. Nevertheless, pain is an indicator of local tissue irritation, and compensation is a sign of movement control impairment, which is a significantly different state when it comes to the direction of clinical intervention. Putting them together as one score reduces interpretability, and can also reduce predictive validity. The proposed study introduces the Compensation-Irritation Matrix (CIM) that divides the raw FMS data into two independent dimensions: the Compensation Index (C, the level at which the rest of the movements are preserved) and the Irritation Index (I, the number and location-weighted load of pain). We confirm the theoretical benefits of CIM over the conventional total-score approach by mathematically counting the full 16,384 possible theoretical score combinations. It is found that given the traditional total-score approach, two random people with the same total score have a 71.4% likelihood of having various numbers of painful items (i.e., same score, but varying quality). Contrastingly, the CIM four-quadrant classification (green-yellow-orange-red) makes perfect sense in every combination with no classification issues. Two case examples indicate that two people with the same total score of 14 are identified as yellow (C = 2.00, I = 0, extensive compensation) and orange (C = 2.80, I = 2.0, localized irritation with high movement quality) on CIM, which implies totally opposite intervention orientation. CIM addresses the dimensional confusion brought about by combining the concepts of compensation and irritation in the traditional total-score method providing a logically consistent alternative model of clinical application of the FMS.